The genus Chlamydotheca Saussure (Crustacea: Ostracoda) in northeastern Argentina - Diaz, Analia Roxana (2011)
The genus Chlamydotheca Saussure, 1858 is a typical representative of the Neotropical ostracod fauna that occupies lotic and lentic environments including temporary and  permanent ponds. Up to the present, four species have been recorded in Argentina: C. iheringi (Sars), C. incisa (Claus) and C. leuckarti (Claus), and C. symmetrica (Vávra). Temporary and permanent ponds of this region were sampled for ostracods, using a fine mesh net. Three species belonging to the genus Chlamydotheca were collected of which C. arcuata (Sars) is recorded for first time for the Chacoan region. Limb morphology was studied under light microscope and line drawings were made using camera lucida. Valves were photographed under scanning electron microscope and redescriptions of C. arcuata and C. iheringi are provided and distributional aspects of the species sampled are discussed.